# i have homework to do over the sring break in analysisof function :y=6-x x=4.5+y use elimnation 2x+3y=3 12x-15y=-4 samethingif any one wants to help thanks

*print*Print*list*Cite

Expert Answers

pohnpei397 | Certified Educator

### 2x+3y=3 12x-15y=-4

For this problem, what you are trying to do is to get one variable term in each equation to be the same as it is in the other, just with the opposite sign. Then you can just eliminate them. In this case, the easiest thing to do is to make it so that the x term in the first equation is -12x. The way to do that is by multiplying by -6.

When you do that, you will have

-12x - 18y = -18

Now you just add the two equations and you get

-33y = -22

Divide both sides by -33 and you get

y = 2/3 or y = .67

Student Comments

neela | Student

y=6-x and x=4.5+y.
We can rewrite the pair of equations as below:
x+y =6 .........(1)and the other
x-y =4.5........ (2)
Eq(1)+ eq(2) eliminates y and we get : 2x=6+4.5 =10.5So x = 10.5/2 = 5.25.
Eq(1)-eq(2) give eliminates x and we get: -2y = 6-4.5 = 1.5. So y = 1.5/-2 = 0.75
Second pair of equations:
2x+3y = 3.............(1)
12x-15y = -4..........(2)
Eq(1)*6 gives: 12x+18y=18......(3)
Eq(2)*1 gives: 12x-15Y=-4......(4)
Eq(3)-eq(4) eliminates x: 33y = 18-(-4) = 22> So y = 22/33 =2/3. Substitute this value of y in (1) to get x:
2x+3(2/3)=3. Or
2x+2=3. Or
2x= 3-2=1. Or
x= 1/2=1/2
2x+3y = 3